A Gestão Associada e Integrada de Resíduos Sólidos: o caso do Plano Regional do Consórcio Intermunicipal de Saneamento Básico da Região do Circuito das Águas (CISBRA) - Gonçalves, Bianca Batosto (2021)
In Brazil, the regulation mark for the GRS – Solid Waste Management has been done via the PNRS – National Solid Waste Policy, instituted by the Law nº 12/305/2010. Concomitantly, a Search for a solution regarding waste treatment became incessant throughout the society, the public domain, private or voluntary sector. In this context, the PNRS proposes the protagonism of county managers to frame shared actions for solid waste treatment and, thus, promoting the adoption of consortiums by the counties (fixed the article 241 of the federal constitution and article 19 of the Law 12.305/2010), since it makes available a gathering of initiatives for common county issues, such as the lack of local managers and the absence of a macro vision of the ecosystems regarding planning and interventions. Considering the many difficulties faced by the Brazilian counties in this process, this research has as objective to verify if a coupled initiative of GRS, the PRGAICA in this case – Region Plan of Integrated Associate Management of Solid Waste for the Water Circuit, also named as “Clean Cities Plan”, contributes to the enhancement of the GRS planning of 12 counties of the CISBRA – Intercity Consortium of Sanitation of the Water Circuit Region, whose signed the plan. For this effect, a methodological strategy was employed that explains as research with an exploratory objective, forwarded by qualitative nature procedures and made viable as a single case study, having as data sources document research, focusing the Clean Cities Plan text and information published by the consortium in its official site, as well as data available in federal and state government electronic portals regarding GRS efficiency of the counties partaking in the consortium. The main advances and difficulties faced in the region are related, respectively, the install of PEVs – Voluntary Disposal Points, the acquisition of trucks for the single gathering service in certain counties, as well as accomplishing many lectures with socioenvironmental content, recycling, and compost workshops, workshops and publications to promote environmental education that allows the encouragement of sustainable practices; the non-fulfillment of the major share of defined goals for the PRGAICA until 2020, and the political deadlock that have been motivating some counties to withdraw from the consortium. The results obtained evince that as the PRGAICA was born as a huge wager of directional tooling for the actions related to GRS in the region, something nonexistent before, almost 10 years after its publication it is still not effectively applied for such ends, becoming instead a piece to fulfill legal demands imposed by the PNRS left behind, risked staying within a field of promises if the goals do not start to become achieved.